The Role of Interventional Radiology in Head and Neck Cancer. (23rd August 2013) - Tulunay‐Ugur, Ozlem E.; Kocdor, Pelin; Rutledge, Jonathan W.; Akdol, Mehmet S.; Erdem, Eren; Vural, Emre
Abstract : Objectives: Evaluate the indications for endovascular techniques in the management of patients with head and neck squamous cell carcinoma. Methods: Retrospective chart review of patients with head and neck cancer who underwent endovascular embolization. Patients' demographics, type of cancer, type of cancer treatment, TNM staging, bleeding site, and medical outcomes were recorded from 2004‐2012, at a university medical center. Results: A total of 14 patients out of 1000 undergoing endovascular procedures had an endovascular procedure due to a head and neck cancer. Their ages ranged from 33‐67 years old (mean = 54 years old). 7 patients had oropharyngeal, 3 laryngeal, 1 hypopharyngeal, 2 oral cavity and 1 skin squamous cell cancer. 8 patients had hypertension. 7 patients underwent chemoradiation therapy as a primary treatment. 9 patients with oral hemorrhage underwent emergency embolization due to bleeding and 5 patients underwent elective embolization. Bleeding arose from the common carotid artery in 2 patients, and external carotid artery and its branches in 6 patients, internal carotid artery in 3 patients, internal maxillary artery in 3 patients. Hemorrhage was successfully controlled in all patients. 2 patients had carotid rupture one month post‐embolization and one patient died. At last follow‐up 6 patients were alive with disease, 4 patients had no evidence of disease and 4 patients were dead due to disease. Conclusions: Interventional radiologic techniques are safe and effective treatment techniques not only for treating life‐threatening hemorrhage but also for pre‐emptive management in the treatment of head and neck cancer.